Identification and partial characterization of potential probiotic lactic acid bacteria in freshwater Labeo rohita and Cirrhinus mrigala. (2nd February 2016) - Shahid, Muhammad; Hussain, Bilal; Riaz, Danish; Khurshid, Mohsin; Ismail, Muhammad; Tariq, Mohsin
Abstract: Carps are the most diversified freshwater fish belonging to family Cyprinidae . Numerous probiotic and pathogenic lactic acid bacteria (LAB) have been characterized from carps. However, the diversity of these ecologically important bacteria is entirely unknown in freshwater fish of Pakistan. The present study aimed to characterize and identify the lactic acid bacteria from two carps viz . Laboe rohita and Cirrhinus mrigala and determine their antagonistic activity. Seventeen bacterial isolates were purified from the gastrointestinal tract and gills of these fish and characterized morphologically. Initially, seven isolates were screened as LAB using agar supplemented with CaCO3 . Subsequently, only two isolates CILB2 and RIL10 were selected as LAB after high‐performance liquid chromatography analysis for lactic acid production. Isolates CILB2 and RIL10 were genetically identified as Enterococcus faecalis and Weissella sp., respectively after 16S rRNA gene sequence analysis. Both strains exhibited significant antagonistic activity against common fish pathogens Streptococcus agalactiae, Staphylococcus aureus and Escherichia coli . Enterococcus faecalis CILB2 and Weissella sp. RIL10 were also found negative for haemolysis and gelatinase activities and were sensitive to ampicillin, amoxicillin, doxycycline, erythromycin, chloramphenicol and co‐trimoxazole antibiotics. The identified LAB strains may further be investigated for their potential probiotic application in fish feed and food preservation techniques.